Complex approach to myocardial electric instability in coronary heart disease patients - V. V. Popov (Российский кардиологический журнал)
Understanding and further investigation of interacting various functional and structural factors, increasing fatal ventricular tachyarrhythmia risk, is an important task. By solving it, we could develop new approaches in prevention and treatment of sudden cardiac death. The review describes the role of non-invasive ECG methods role in coronary heart disease patients, as these methods can provide valuable information on individual predisposition for life-threatening arrhythmias.